Do they really return to early? Investigating the causal effect of rehab time on injury risk after return to play in elite football - Hecksteden, A.; Brink, M.; Lemmink, K.; Meyer, T.; Hauser, T. (Current Issues in Sport Science, 2024)
In elite football, injury risk is considerable. Consequently, optimal rehabilitation and an adequate time point of return-to-play (RTP) are crucial. The elevated injury risk in the weeks after RTP (e.g. Orchard & Best, 2002; Wangensteen et al., 2016) and the time course of biological healing processes (Orchard & Best, 2002) nourished the speculation that players generally return to early. While the previously reported negative association between rehab time and injury risk after RTP (e.g. Beischer et al., 2020; Della Villa et al., 2021; Orchard & Best, 2002) points in the same direction, the truism "Correlation does not imply causation." must be considered. To the best of our knowledge, the causal effect of rehab time on injury risk has not been investigated so far. This work aims to contribute towards closing this gap in knowledge. Specifically, to scrutinize if a reduction in injury risk may be expected when RTP is delayed.